Hawthorn (Crataegus spp.) in the treatment of cardiovascular disease - Tassell, Mary C.; Kingston, Rosari; Gilroy, Deirdre; Lehane, Mary; Furey, Ambrose (Pharmacognosy Reviews, 2010)
The medicinal properties of hawthorn (Crataegus spp., a genus comprising approximately 300 species) have been utilized by many cultures for a variety of therapeutic purposes for many centuries. In the Western world cardiovascular disease (CVD) has become one of the single most significant causes of premature death. Echoing this situation, more recent research into the therapeutic benefits of hawthorn preparations has focused primarily upon its cardiovascular effects. This review covers research into the various mechanisms of action proposed for Crataegus preparations, clinical trials involving Crataegus preparations, and the herb’s safety profile. Clinical trials reviewed have been inconsistent in terms of criteria used (sample size, preparation, dosage, etc) but have been largely consistent with regard to positive outcomes. An investigation into data available to date regarding hawthorn preparations and herb/drug interactions reveals that theoretical adverse interactions have not been experienced in practice. Further, adverse reactions relating to the use of hawthorn preparations are infrequent and mild, even at higher dosage ranges. A recent retrospective study by Zick et al. has suggested a negative outcome for the long-term use of hawthorn in the prognosis of heart failure. These findings are examined in this paper. Although further research is needed in certain areas, current research to date suggests that hawthorn may potentially represent a safe, effective, nontoxic agent in the treatment of CVD and ischemic heart disease (IHD).
Keywords: Cardiovascular disease; Crataegus; hawthorn; whitethorn